Thrombin-induced cytoskeleton dynamics in spread human platelets observed with fast scanning ion conductance microscopy - Seifert, Jan (Sci Rep, 2017)
Platelets are small anucleate blood cells involved in haemostasis. Platelet activation, caused by agonists such as thrombin or by contact with the extracellular matrix, leads to platelet adhesion, aggregation, and coagulation. Activated platelets undergo shape changes, adhere, and spread at the site of injury to form a blood clot. We investigated the morphology and morphological dynamics of human platelets after complete spreading using fast scanning ion conductance microscopy (SICM). In contrast to unstimulated platelets, thrombin-stimulated platelets showed increased morphological activity after spreading and exhibited dynamic morphological changes in the form of wave-like movements of the lamellipodium and dynamic protrusions on the platelet body. The increase in morphological activity was dependent on thrombin concentration. No increase in activity was observed following exposure to other activation agonists or during contact-induced activation. Inhibition of actin polymerization and inhibition of dynein significantly decreased the activity of thrombin-stimulated platelets. Our data suggest that these morphological dynamics after spreading are thrombin-specific and might play a role in coagulation and blood clot formation.